Antioxidant activity of water extract of Scoparia dulcis - Ratnasooriya, W.D.; Jayakody, J.R.A.C.; Premakumara, G.A.S. (My University, 2005)
An aqueous extract of Scoparia dulcis showed marked antioxidative activity in vitro, which supports the therapeutic efiects claimed by traditional practitioners. © 2004 Published by Elsevier B.V.